Spatial distribution of morphometric parameters of glacial cirques in the Central Pyrenees (Aran and Boí valleys) - Lopes, Luis (2019)
Glacial cirques are typical landscape features of mid-latitude mountain environments like the Central Pyrenees. Their morphology as well as their spatial distribution provides insights about past glaciers and climates. In this study, we examine the distribution, morphometrical and topographical characteristics of glacial cirques in two U-shaped glacial valleys located in the Central Pyrenees – the Aran and the Boí valleys. They are located in different aspects of this mountain range (north vs south) under different climatic influences that promoted distinct glaciation patterns during the late Pleistocene. The spatial mapping of these landforms was carried out using high-resolution imagery and field observations. We analysed the data of the morphometrical and topographical variables of the glacial cirques by using different statistical and geospatial methods in order to unveil the factors controlling their formation and development. A total of 186 glacial cirques were mapped in the study area, including 119 in the Aran and 67 in the Boí valleys. The local topography and microclimate conditions lead to substantial differences in both areas in terms of the morphology and dimensions of the cirques. Glacial cirques in Boí are distributed at slightly higher elevations than in Aran and they are also larger, though their dimensions decrease with elevation in both valleys. Aran cirques are mostly oriented NE, while Boí landforms do not show any prevailing aspect. Even though lithology does not control the distribution of the glacial cirques, some specific lithological settings may favour the development of larger cirques. In general, glacial cirques in the Aran and the Boí valleys show morphometrical properties similar to those reported in other mid-latitude mountain ranges.